2019
DOI: 10.2217/cer-2018-0090
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization risk factors in antipsychotic-treated schizophrenia, bipolar I disorder or major depressive disorder

Abstract: Aim: To examine hospitalization risk factors in antipsychotic-treated patients with schizophrenia, bipolar I disorder (BD-I) or major depressive disorder (MDD). Patients & methods: Using Truven Health MarketScan® Commercial, Medicaid and Medicare Supplemental data (01/01/2012–06/30/2016), logistic regression models were performed to identify risk factors for both psychiatric and all-cause hospitalization in three separate analyses. Results: Significant risk factors included prior hospitalization (schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Nine analyses from three studies [ 39 , 46 , 67 ] investigated the impact of diabetes (n = 5), cardiovascular disease (n = 2) and COPD (n = 2) on hospitalisation in a patient population with pre-existing schizophrenia (n = 2) or bipolar disorder (n = 7). The outcome was all-cause ED attendances for four studies and all-cause admissions for five.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine analyses from three studies [ 39 , 46 , 67 ] investigated the impact of diabetes (n = 5), cardiovascular disease (n = 2) and COPD (n = 2) on hospitalisation in a patient population with pre-existing schizophrenia (n = 2) or bipolar disorder (n = 7). The outcome was all-cause ED attendances for four studies and all-cause admissions for five.…”
Section: Resultsmentioning
confidence: 99%
“…Nine analyses from three studies [39,46,67] investigated the impact of diabetes (n = 5), cardiovascular disease (n = 2) and COPD (n = 2) on hospitalisation in a patient population with pre-…”
Section: Hospital Utilisation In People With Smi Comparing People Wit...mentioning
confidence: 99%
“…While this study was not designed to assess the specific causes of increased hospitalization, prior research found that hospitalization following the use of AAPs is driven by several known risk factors such as age, sex, drug formulation [e.g., oral vs. long-acting injectable (LAI)], non-adherence, and living in a supervised setting ( 15 ). The current study found that older adults generally had higher RORs of hospitalization than younger adults partly because AAPs are associated with potentially serious AEs in vulnerable older adults due to age-related reduction in the ability to metabolize and excrete drugs ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 45 Psychiatric hospital admission among patients with SCZ is associated with younger age; prior hospital admission; and comorbidities such as substance misuse, depression, anxiety and personality disorders. 46 Annual hospital admission rates range from approximately 23 to 27% in recent literature. 46 , 47 In our study, the annual psychiatric hospital admission rate was only 7%.…”
Section: Discussionmentioning
confidence: 99%
“… 46 Annual hospital admission rates range from approximately 23 to 27% in recent literature. 46 , 47 In our study, the annual psychiatric hospital admission rate was only 7%. Older patient age might have contributed to the low hospital admission rate, but it is also likely that patient selection for CABG favours those with fewer psychiatric symptoms and better overall psychosocial functioning.…”
Section: Discussionmentioning
confidence: 99%